Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.484
|View full text |Cite
|
Sign up to set email alerts
|

XGLUE: A New Benchmark Datasetfor Cross-lingual Pre-training, Understanding and Generation

Abstract: In this paper, we introduce XGLUE, a new benchmark dataset that can be used to train large-scale cross-lingual pre-trained models using multilingual and bilingual corpora and evaluate their performance across a diverse set of cross-lingual tasks. Comparing to GLUE (Wang et al., 2019), which is labeled in English for natural language understanding tasks only, XGLUE has two main advantages: (1) it provides 11 diversified tasks that cover both natural language understanding and generation scenarios; (2) for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 13 publications
(11 reference statements)
1
124
0
Order By: Relevance
“…We show that our new contrastive learning alignment objectives outperform previous work (Cao et al, 2020) when applied to bitext from previous works or the OPUS-100 bitext. However, our experiments also produce a negative result.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…We show that our new contrastive learning alignment objectives outperform previous work (Cao et al, 2020) when applied to bitext from previous works or the OPUS-100 bitext. However, our experiments also produce a negative result.…”
Section: Introductionmentioning
confidence: 65%
“…enforcing similar words from different languages have similar representation, improvements can be attained through the use of explicit cross-lingually linked data during pretraining, such as bitexts (Conneau and Lample, 2019;Huang et al, 2019;Ji et al, 2019) and dictionaries . As with cross-lingual embeddings (Ruder et al, 2019), these data can be used to support explicit alignment objectives with either linear mappings (Wang et al, 2019(Wang et al, , 2020 or fine-tuning (Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the English dataset is automatically translated into the desired language(s) using machine translation (MT); an augmented dataset composed of the original English text and all the translated copies is created; the mBERT model is fine-tuned on a subset of the dataset; and the resultant model is then used to solve the relevant downstream task in the desired language. Previous works have suggested that translating the original dataset to as large a number of languages as possible is beneficial (Liang et al, 2020). In this work, we show a more nuanced picture, where often selecting a subset of related languages is preferable.…”
Section: Introductionmentioning
confidence: 82%
“…This allows us to draw more holistic conclusions on the efficacy -and pitfalls -of transfer learning in the argument mining domain. It is interesting to compare these conclusions with other wide-scope multilingual NLU research, such as the XTREME (Hu et al, 2020) and XGLUE (Liang et al, 2020).…”
Section: Related Workmentioning
confidence: 90%
“…XLM-Roberta is a variant of BERT with a different objective, and is trained in an unsupervised manner on a multi-lingual corpus. These models have achieved state-of-the-art results in NLU and NLG tasks across multiple languages for popular benchmarks such as XGLUE [13], XTREME [10].…”
Section: Methodsmentioning
confidence: 99%